2020
DOI: 10.36227/techrxiv.12705722.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seeing the Big Picture: Improving The Prosthetic Design Cycle Using 360° 3D Digital Image Correlation

Abstract: Additive manufacturing is one of the most promising emerging technologies for building prosthetic sockets. However, there is no reliable way to estimate the factor of safety and the lifetime of 3D printed prosthetic sockets. Here, we explore 360° 3D digital image correlation (DIC) and discover how this new tool can increase our understanding of prosthetic structural failures. We establish that this new technology can dramatically improve the prosthetic design cycle by identifying local strain concentrations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…In the authors' previous work [11] as well as dynamic testing experiments by Saey et al [12], it was revealed how crucial the junction between the AM socket and modular component interface is. Without careful design consideration, these interfaces can fail at much lower strengths or cycles than predicted.…”
Section: Background 21 Materials Challengesmentioning
confidence: 98%
“…In the authors' previous work [11] as well as dynamic testing experiments by Saey et al [12], it was revealed how crucial the junction between the AM socket and modular component interface is. Without careful design consideration, these interfaces can fail at much lower strengths or cycles than predicted.…”
Section: Background 21 Materials Challengesmentioning
confidence: 98%
“…Sockets have been successfully produced using FDM, but past researchers noted that these structures were not strong for implementation [78], [80]- [83]. A unique approach to FDM, the Squirt Shape system was developed at Northwestern University in 1992.…”
Section: Technologies For Additive Manufacturing Of Prosthetic Modelsmentioning
confidence: 99%
“…These techniques have been utilized in assessing damage in wood samples [35][36][37], bridge and concrete surfaces [38][39][40], pavement [34,41,42], and steel [43][44][45]. Other applications of DIC include biomechanical applications [46], biological tissues and biomaterials [47][48][49], aerospace [50,51], computer vision [52], medical appli-cations [53], industrial and automotive applications [54]. In contrast to other traditional Non-Destructive Techniques (NDT) measuring methods and specific visual methods like radioactive computerised tomography, which are otherwise costlier and quite challenging to employ beyond the laboratory environment because they entail detailed setup and low vibrational surroundings, DIC is economically feasible and easier to grasp.…”
Section: Digital Image Correlationmentioning
confidence: 99%